Field emission of MWCNTs/PANi nanocomposites prepared by ex‐situ and in‐situ polymerization methods. Issue 8 (24th June 2013) - Shumaila, Samina Husain; Parveen, Shama; Ali, Javid; Kumar, Avshish; Husain, M.
<x xml:space="preserve">Abstract</x> The present work describes the field‐emission properties of multiwalled carbon nanotubes (MWCNTs) coated with conducting polymer polyaniline (PANi). MWCNTs/PANi nanocomposites have been prepared by ex‐ situ polymerization methods and inex‐ situ chemical polymerization and are analyzed by SEM and Raman spectroscopy. It is fairly clear from SEM images that PANi is coated on the surface of MWCNT. SEM image of PANi powder also shows that the powder obtained is PANi nanofibers. It is also observed from SEM images that the shell diameter of MWCNTs depends on PANi content in thenanocomposites. The average outer diameter of MWCNTs increases from 7–15 to 50–80 nm upon PANi coating. Field‐emission study shows that although there is decrease in the value of turnex‐on field Eto and increase in the value field enhancement factor β of the nanocomposites as we go from direct solid‐state mixing method to inex‐ situ chemical polymerization method, the parameters obtained by inex‐ situ polymerization chemical method shows superior field emission. The turn‐on field of the nanocomposites are between 2.5 and 4.5 V/μm and the field enhancement factors are significantly high, between 1.2 × 103 and 9.2 × 103 while. PANi nanofibers does not show any field emission. POLYM. COMPOS. 34:1298–1305, 2013. © 2013 Society of Plastics Engineers